Automated Processing of Doppler Radar Data for Severe Weather Warnings - Joe, Paul; Dance, Sandy; Lakshmanan, Valliappa; Heizenreder, Dirk; James, Paul; Lang, Peter; Hengstebeck, Thomas; Feng, Yerong; Li, P.W.; Yeung, Hon-Yin; Suzuki, Osamu; Doi, Keiji; et al. (IntechOpen, 2012)
None